Surface balance study of the interaction between microorganisms and lipid monolayer at the air/water interface. - Kjelleberg, S (1976)
Using the surface balance technique, we have compared the interaction between Acholeplasma laidlawii and some marine bacteria towards different types of monolayered lipid films. Cells from A. laidlawii and Serratia marinorubra penetrate the film, whereas cells from Psuedomonas fluorescens form a layer underneath the film. The forces that bind microorganisms to the air/water interface are not strong enough to scatter a condensed monolayer but increase the strength of loosely packed monolayers.